Determination of jet-engine fuel inclination to gum formation and the problems of aircraft operation - Кузнецова, Е. Я. (Proceedings of National Aviation University (archive), 2000)
Described is a new method of determining fuel inclination to gum formation. The achieved results give the ground to recommend this index and the worked out methods for inclusion into the list of indexes of quality check analysis. This will provide the possibility to detect the beginning of deterioration of fuel quality in the process of preparation of the fuel for refueling